2007
DOI: 10.1128/iai.01496-06
|View full text |Cite
|
Sign up to set email alerts
|

Native Microbial Colonization of Drosophila melanogaster and Its Use as a Model of Enterococcus faecalis Pathogenesis

Abstract: Enterococci are commensal organisms of the gastrointestinal (GI) tracts of a broad range of mammalian and insect hosts, but they are also leading causes of nosocomial infection. Little is known about the ecological role of enterococci in the GI tract consortia. To develop a tractable model for studying the roles of these organisms as commensals and pathogens, we characterized the Drosophila melanogaster microflora and examined the occurrence of enterococci in the gastrointestinal consortium of Drosophila. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
239
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(268 citation statements)
references
References 69 publications
19
239
3
Order By: Relevance
“…In this study, individual microbial taxa were not generally found to be shared universally, either within or among drosophilid species in laboratory conditions. In particular, the data do not substantiate the common bacterial taxa found by Cox and Gilmore (2007) across laboratory and field conditions for one species, D. melanogaster. Our results complement and extend the research of Chandler et al (2011), in which shallow sampling with Sanger sequencing failed to yield a common subset of bacterial OTUs among field samples of multiple Drosophila species.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…In this study, individual microbial taxa were not generally found to be shared universally, either within or among drosophilid species in laboratory conditions. In particular, the data do not substantiate the common bacterial taxa found by Cox and Gilmore (2007) across laboratory and field conditions for one species, D. melanogaster. Our results complement and extend the research of Chandler et al (2011), in which shallow sampling with Sanger sequencing failed to yield a common subset of bacterial OTUs among field samples of multiple Drosophila species.…”
Section: Discussionmentioning
confidence: 50%
“…An important caveat to our understanding is whether the gut microbiota includes a common phylogenetic subset. Cox and Gilmore (2007) noted three taxa, Acetobacter aceti, A. pasteurianus and Enterococcus faecalis, in two laboratory strains and one wild population, but Corby-Harris et al (2007) described 74 taxa that were 'unevenly spread' among wild populations of D. melanogaster. Chandler et al (2011) reported that members of Enterobacteriaceae and Lactobacillales are very widely distributed, but apparently not universal, across 20 populations of multiple species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of wild and domesticated mice (Wilson et al, 2006), turkeys (Scupham et al, 2008), parrots (Xenoulis et al, 2010), fruitflies (Cox and Gilmore, 2007) and hydra (Fraune and Bosch, 2007) indicate that members of the same species tend to possess gut bacterial communities of similar taxonomic composition at the phylum or class level regardless of domestication status, with some differences between wild and domestic individuals emerging at shallower phylogenetic resolution. These previous studies have revealed varying effects of domestication on gut bacterial diversity, with increased diversity in wild mice (Wilson et al, 2006) and fruitflies (Cox and Gilmore, 2007) compared with domesticated controls, and decreased diversity in wild versus domesticated parrots (Xenoulis et al, 2010). Our clone library sequencing and pyrosequencing of the zebrafish intestinal microbiota revealed variation between recently caught and domesticated zebrafish, however, the scale of these variations were no larger than those observed between or within different zebrafish lab facilities (Figures 2, 4, and Supplementary Figure S1).…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbes also play a role in invertebrate biology (Dillon and Dillon, 2003) and digestive process [Brune, 2011 [Lundgren, 2010, and recently the composition of microbe gut populations has been described in a variety of insect species, including bees (Jeyaprakash et al, 2003;Mohr and Tebbe, 2006), beetles (Egert et al, 2005;Lehman et al, 2009;Nardi et al, 2006;Zhang and Jackson, 2008), flies (Cox and Gilmore, 2007;Ren et al, 2007;Ryu et al, 2008;Shin et al, 2011;Wong et al, 2011), lepidopterans (Pauchet et al, 2010;Xiang et al, 2006) and termites (Hongoh et al, 2003). In Drosophila, the microbiome regulates host metabolic homeostatic and developmental programs by modulating the insulin/insulin-like growth factor (Shin et al, 2011).…”
Section: Microbiota: a Key Component Of Nutritional Immunologymentioning
confidence: 99%